Modulation of Inflammation and Immune Response by Herbal Extract in Escherichia coli Infected Broiler Chickens - H Patel, Jatin; R Patel, Ankit; D Varia, Rasesh; D. Vihol, Priti; D Padheriya, Yogesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This experiment was conducted to evaluate the immunomodulatory and anti-inflammatory effects of a fermented polyherbal formulation in Escherichia coli infected broiler chickens over a period of 28 days (from day 0 to 28th day of age). A total of 120 day-old broiler chicks (Vencobb 400) were divided into four equal groups each of 30 birds, viz., Environmental control (G1), infection control (G2), non-fermented extract treated (G3) and fermented extract treated (G4). E. coli infection was experimentally induced in all groups, except the environment control group. Significant reductions in CRP and TNF-α concentrations were observed in the polyherbal treated groups compared to the infection group. Antibody response to Newcastle disease virus (NDV) was assessed using the haemagglutination inhibition (HI) test. Administration of the polyherbal formulation resulted in higher HI titres in both treated groups, reflecting an improved humoral immune response when compared with the infection group. In conclusion, fermented polyherbal extract effectively suppressed systemic inflammation, as evidenced by lower CRP and TNF-α levels, and strengthened humoral immune responses through increased NDV antibody titres in E. coli infected broiler chickens.